Nanocomposite Hydrogels: Bioactive‐Tissue‐Derived Nanocomposite Hydrogel for Permanent Arterial Embolization and Enhanced Vascular Healing (Adv. Mater. 33/2020). Issue 33 (18th August 2020) - Hu, Jingjie; Altun, Izzet; Zhang, Zefu; Albadawi, Hassan; Salomao, Marcela A.; Mayer, Joseph L.; Hemachandra, L. P. Madhubhani P.; Rehman, Suliman; Oklu, Rahmi
Abstract : In article number 2002611, Rahmi Oklu and co‐workers introduce a nanocomposite hydrogel based on decellularized cardiac extracellular matrix as a novel therapeutic embolization agent, which provides superior mechanical stability, catheter injectability, and biological activity to prevent recanalization. Image credit: Michael Austin, Internal Art Medical Illustration, LLC.